Bohlokwa bja dinonwane tša Sepedi thutong ya mabokgoni a ngwagakgolo wa 21 - Maledu, Ablonia Dihloriso (Journal for Language Teaching, 2024)
English title: The significance of Sepedi folktales in teaching 21st century skills The aim of the study is to highlight the importance of folktales in the teaching of 21st Century skills in the Sepedi language classrooms. The learning skills to be discussed are communication, creativity, collaboration and critical thinking. The study followed qualitative approach and the data collection method used was document analysis method. The theory adopted for the study is Ethnography of Communication by Hymes (1962), supported with Text-Based Approach for Language Teaching as stated in Sepedi Curriculum and Assessment Policy Statement (CAPS: 2011). The findings for the study revealed that folktales have been around as long as the existence of man and they played a very important role in the teaching of indigenous people on how to go about in their lives. The study recommends that folktales should be part of the formal education and be given high recognition like other genres that are being taught in schools, also should be formally assessed. The study will benefit teachers and learners due to the fact that learners will be able to relate to the texts and learning will be easy for them.